Prognostic indicators for first and repeated hospitalizations in heart failure patients with reduced left ventricular ejection fraction - Selthofer-Relatić, Kristina; Tomić, Mato; Stažić, Anto; Arambašić, Jerko; Kralik, Kristina; Mirat, Jure (2020)
Heart failure with reduced ejection fraction (HFrEF) is a progressive clinical syndrome defined by changes in the myocardial structure, which lead to predominant systolic myocardial function impairment, with a left ventricle ejection of fraction ≤40%. The rehospitalization burden in HFrEF patients (pts) remains very high, with poor quality of life, increased mortality and large healthcare expenditures. In this research project, we investigated the risk factors for first and repeated hospitalization in pts with HFrEF. This retrospective study included 50 adult pts with a diagnosis of HFrEF and who were within the age range of 55 to 89 years old and of both sexes. Demographic and clinical data (HFrEF etiology, renal function parameters, complete blood count, markers of nflammation, electrocardiogram, troponin I, NTproBNP, echocardiographic parameters and comorbidities data) were collected from the pts’ medical histories. Statistical analysis was performed via Fischer’s exact test, the Shapiro-Wilk test and the Spearman correlation coefficient. This study included 70% male and 30% female HFrEF pts. Males were younger in both group of pts and had a higher incidence of rehospitalization. The most important HFrEF etiologic risk factors are arterial hypertension (82%), coronary heart disease (54%), atrial fibrillation (52%) and diabetes mellitus (40%). The most important noncardiac comorbidity related with the first HFrEF hospitalization is pneumonia (P=0.03), while progression of left ventricle systolic and diastolic dysfunction is related to rehospitalization risk (left ventricle end systolic diameter, P=0.003; diastolic dysfunction degree, P=0.04). The troponin level was associated with an increased risk of rehospitalization, but this was not statistically significant at this sample size (troponin I, p=0.10).
Srčano popuštanje s reduciranom ejekcijskom frakcijom (HFrEF) progresivni je klinički sindrom definiran strukturnim promjenama miokarda koji dovodi prvenstveno do oštećenja sistoličke funkcije s redukcijom ejekcijske frakcije lijeve klijetke ≤40 %. Učestalost ponovne hospitalizacije pacijenata s HfrEF-om vrlo je visoka, smanjuje kvalitetu života, povećava stopu smrtnosti i veliko je financijsko opterećenje zdravstvenome sustavu. U istraživanju su proučavani rizični čimbenici za prvu i ponovnu hospitalizaciju kod pacijenata s HfrEF-om. U ovu retrospektivnu studiju uključeno je 50 odraslih pacijenata s dijagnozom HfrEF-a, životne dobi između 55 i 89 godina, oba spola. Demografski i klinički podaci (etiologija HfrEF-a, parametri bubrežne funkcije, kompletna krvna slika, biljezi upale, elektrokardiogram, troponin I, NTproBNP, ehokardiografski parametri, komorbiditeti) prikupljeni su iz medicinske dokumentacije pacijenata. Statistička analiza učinjena je Fischerovim egzaktnim testom, Shapiro-Wilk testom i Spearmanovim koeficijentom korelacije. U studiju je uključeno 70% muškaraca i 30% žena s HfrEF-om, muškarci su u obje praćene skupine bili mlađe životne dobi te su imali veću incidenciju rehospitalizacije. Najznačajniji etiološki čimbenici rizika za HFrEF su arterijska hipertenzija (82%), koronarna bolest (54%), atrijska fibrilacija (52%), šećerna bolest (40%). Od nekardioloških komorbiditeta vezanih uz prvu hospitalizaciju pacijenata s HfrEF-om najznačajnija je pneumonija (P = 0,03), dok je pogoršanje sistoličke i dijastoličke funkcije lijeve klijetke vezano uz ponovnu hospitalizaciju (end-sistolički promjer lijeve klijetke, P = 0,003; stupanj dijastoličke disfunkcije, P = 0,04). Biomarker troponin I pokazao je tendenciju porasta u rehospitalizaciji, ali bez statističke značajnosti na ovoj veličini uzorka (troponin I, p = 0,10).
Bibliografske bilješke na kraju teksta.
Abstract ; Sažetak.
Keywords: Zatajenje srca -- Ejekcijska frakcija -- Hospitalizacija -- Prognostički pokazatelji -- Čimbenici rizika